Early rather than delayed administration of lisinopril protects the heart after myocardial infarction in rats - Zornoff, Leonardo Antonio Mamede [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Paiva, SAR; Spadaro, J. (Dr Dietrich Steinkopff Verlag, 2000)
Background: ACE inhibitors have shown beneficial results in several studies after myocardial infarction (MI). However, these studies have shown conflicting results about the ideal starting time of the ACE inhibitors administration after MI and the importance of infarct size.Objectives: This study was designed to assess the long-term effects of lisinopril on mortality, cardiac function, and ventricular fibrosis after MI, in rats.Methods: Lisinopril (20 mg/kg/day) was given on day 1 or 21 days after coronary occlusion in small or large infarctions.Results: the mortality rate was reduced by 39% in early treatment and 30% in delayed treatment in comparison to the untreated rats. Early treatment reduced cardiac dysfunction in small MIs; however, delayed treatment did not. No statistical difference was observed among the groups for large MIs. No statistical difference was observed among the groups with large or small MIs on myocardial hydroxyproline concentration.Conclusions: Both early and delayed treatments with lisinopril increased survival. Treatment exerts no marked effects on fibrosis; early treatment has exerted beneficial influences on cardiac function whereas delayed treatment had no consistent effects. The protective effect of lisinopril is detectable only in small (< 40% of LV) MIs.
Keywords: myocardial infarction; ventricular remodeling; angiotensin-converting enzyme inhibitor; lisinopril; rat